2010
DOI: 10.1111/j.1755-3768.2010.2133.x
|View full text |Cite
|
Sign up to set email alerts
|

p62/sequestosome 1 as a regulator of proteasome inhibitor‐induced autophagy in human retinal pigment epithelial cells

K KAARNIRANTA

Abstract: Purpose:The pathogenesis of age-related macular degeneration involves impaired protein degradation in retinal pigment epithelial (RPE) cells. The ubiquitin-proteasome pathway and the lysosomal pathway including autophagy are the major proteolytic systems in eukaryotic cells. Prior to proteolysis, heat shock proteins (HSPs) attempt to refold stress-induced misfolded proteins and thus prevent the accumulation of cytoplasmic protein aggregates. Recently, p62/sequestosome 1 (p62) has been shown to be a key player … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…At P14 and P18, with the presence of a fully vascularized retina, a decrease in p-ULK1 and LC3 II protein levels is determined concomitantly with an increase of p62. The observed accumulation of p62 with a decrease of LC3 II protein levels at P14 could be associated with a transition from autophagy-dependent to -independent mechanisms of retinal homeostasis, as previously suggested in retinal pigment epithelium cells [51,52].…”
Section: Discussionsupporting
confidence: 75%
“…At P14 and P18, with the presence of a fully vascularized retina, a decrease in p-ULK1 and LC3 II protein levels is determined concomitantly with an increase of p62. The observed accumulation of p62 with a decrease of LC3 II protein levels at P14 could be associated with a transition from autophagy-dependent to -independent mechanisms of retinal homeostasis, as previously suggested in retinal pigment epithelium cells [51,52].…”
Section: Discussionsupporting
confidence: 75%
“…The characterization confirmed that both control-RPE cells and AMD-RPE cells showed characteristics of mature RPE cells. prevent protein clearance and induce inflammasomes in ARPE-19 cells and in embryonal stem-cell-derived RPE cells [22,33,34]. Activation of inflammasomes in iPSC-RPE cells significantly reduced cellular viability, as observed by an elevated release of lactate dehydrogenase (LDH).…”
Section: Control and Amd-patient-derived Ipsc-rpe Monolayers Showed Mature Rpe Characteristicsmentioning
confidence: 99%
“…To stimulate inflammasome activation, iPSC-RPE cells were first primed with IL-1α and inflammasomes were then activated by inhibiting cellular clearance mechanisms using MG-132 (inhibition of the proteasome) and bafilomycin A1 (inhibition of autophagy). The conditions and concentrations had been previously tested and found to prevent protein clearance and induce inflammasomes in ARPE-19 cells and in embryonal stem-cell-derived RPE cells [22,33,34]. Activation of inflammasomes in iPSC-RPE cells significantly reduced cellular viability, as observed by an elevated release of lactate dehydrogenase (LDH).…”
Section: Inflammasome Activation In Amd-and Control-patient-derived Ipsc-rpe Cell Linesmentioning
confidence: 99%